Developing Animated Video of Describing People for Vocabulary Learning - Diva Erlina Septiani; Purwanti, Indah Tri; Prawati, Atni (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
This study aims to develop an animated learning video on describing people. The subjects of this study were first-year students majoring in English education at Riau University, totaling 39 students. The researchers applied Research and Development (R&D) by applying the ADDIE model. The instruments used were interviews, validation sheets from media experts, material experts, and pedagogic experts, and student response questionnaires. The results showed that the average results of the experts' assessment for animated videos with idioms for describing people material were 92.4% which was classified as 'highly valid' and for animated videos with material describing people; personality was 93% which was classified as 'highly valid', then from the results of student response questionnaires obtained a percentage score of 80.66% categorized as 'feasible' for video animations with idioms for describing people material and 79.22% categorized as 'feasible' for video animations with material describing people; personality. Therefore, the video animation is declared valid and feasible to be used as vocabulary learning media for English language education students. In addition, the use of animated video learning media describing people can have a positive impact on learning activities, namely attracting students' interest in learning and helping students understand the material.